Evaluation of changes in liver functions of normal pregnant women in Shendi locality, Sudan - Hummieda, Sami; Eltigani, Mohammed A; Al Deen, Babiker Gamal; AL Baz, Hanaa (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Changes in value of certain serum liver function tests occur during normal pregnancy and an understanding of these physiological changes is necessary for the management of liver diseases. Material & Methods: This cross-sectional study was conducted at Shendi locality. The patients underwent a clinical assessment, which included history (a questionnaire) and clinical examination. 160 women were divided into four group’s non pregnant as control group, 1st, 2nd and 3rd trimester of pregnancy respectively. The age limits was 12 to 40 years. Serum sample was taken and assessed for routine liver function tests. Results: All values were within normal limits. Serum ALT and AST activity was slightly decreased (not significant) in first, second and third trimester than control pregnant women. The mean value of serum total, direct and in direct bilirubin concentrations were also slightly decreased (not significant) in first and second trimester than control but increased third trimester pregnant women. Conclusion: It concluded that the serum ALT, AST and total bilirubin are affected by pregnancy in the3rd trimester more than the1st trimester.